“I Want, Therefore I Am” – Anticipated Upward Mobility Reduces Ingroup Concern - Chipeaux, Marion; Kulich, Clara; Iacoviello, Vincenzo; Lorenzi-Cioldi, Fabio (Frontiers in Psychology, 2017)
Empirical findings suggest that members of socially disadvantaged groups who join a better-valued group through individual achievement tend to express low concern for their disadvantaged ingroup (e.g., denial of collective discrimination, low intent to initiate collective action). In the present research, we investigated whether this tendency occurs solely for individuals who have already engaged in social mobility, or also for individuals who psychologically prepare themselves, that is ‘anticipate’, social mobility. Moreover, we examined the role of group identification in this process. In two studies, we looked at the case of 'frontier workers', that is people who cross a national border every day to work in another country where the salaries are higher thereby achieving a better socio-economic status than in their home-country. Study 1 (N = 176) examined attitudes of French nationals (both the socially mobile and the non-mobile) and of Swiss nationals toward the non-mobile group. As expected, results showed that the mobile French had more negative attitudes than their non-mobile counterparts, but less negative attitudes than the Swiss. In Study 2 (N = 216), we examined ingroup concern at different stages of the social mobility process by comparing the attitudes of French people who worked in Switzerland (mobile individuals), with those who envisioned (anticipators), or not (non-anticipators), to work in Switzerland. The findings revealed that anticipators’ motivation to get personally involved in collective action for their French ingroup was lower than the non-anticipators’, but higher than the mobile individuals’. Moreover, we found that the decrease in ingroup concern across the different stages of social mobility was accounted for by a lower identification with the inherited ingroup. These findings corroborate the deleterious impact of social mobility on attitudes toward a low-status ingroup, and show that the decrease in ingroup concern already occurs among individuals who anticipate moving up the hierarchy. The discussion focuses on the role of the discounting of inherited identities in both the anticipation and the achievement of a higher-status identity.